Cluster sets lead to better performance maintenance and minimize training-induced fatigue than traditional sets - Páez-Maldonado, José Antonio; Cornejo-Daza, Pedro Jesús; Sánchez-Valdepeñas, Juan; Sánchez-Moreno, Miguel; Piqueras-Sanchiz, Francisco; Ortega-Becerra, Manuel; Pareja-Blanco, Fernando (Frontiers in Sports and Active Living, 2024)
Objective The aim of this study was to examine the acute effects on mechanical, neuromuscular, metabolic, and muscle contractile responses to different set configurations in full-squat (SQ). Methods Twenty-two men performed three SQ sessions that consisted of 3 sets of 12 repetitions with 60% 1RM with 4 minutes inter-set rests: a) traditional set (TS): no rest within the set; b) cluster-6 (CS6): a 30 seconds intraset rest after the 6th repetition of each set; and c) cluster-2 (CS2): a 30 seconds intraset rest every 2 repetitions. Mechanical (i.e., force, velocity, and power) and electromyography (EMG) values were recorded for every repetition. A battery of tests was performed: a) tensiomyography (TMG), b) blood lactate c), countermovement jump (CMJ), d) maximal isometric SQ, and e) performance with the load that resulted in a velocity of 1 m·s−1 at baseline (V1-load). Repeated measured ANOVA analyses were used to compare the 3 protocols. Results As the number of intraset rests increased (TS < CS6 < CS2), mechanical performance was better maintained (p < 0.01) and EMG variables were less altered (p = 0.05). At post, CS2 and CS6 displayed lower lactate concentration, lesser reductions in CMJ height, and smaller alterations in TMG-derived variables than TS (p < 0.05). Conclusion The introduction of short and frequent intraset rest periods during resistance exercise alleviates training-induced fatigue, resulting in better maintenance of performance. This approach can be applied during the in-season period when minimizing fatigue is a priority.